Conceptual Framework for Assessing Sustainability of Swamp Buffalo Production Systems - Atmoko, Bayu Andri; Prabowo, Bryan Wisnu; Sumantri, Ika; Prastowo, Sigit; Widyas, Nuzul; Mastuti Widi, Tri Satya (Journal of Buffalo Science, 2023)
Swamp Buffalo farming plays an important role in farmers’ livelihood and in satisfying red meat demand in South Kalimantan, Indonesia. The extensive (wetland) swamp buffalo production system (SPS) and the extensive and semi-intensive dryland system (DPS) are two production systems. The production systems have high complexity and require the integrated sustainability assessment approach to measure the contribution level of sustainability indicators. This study aimed to demonstrate the conceptual framework for analyzing the sustainability of buffalo production systems in South Kalimantan. The buffalo production systems in South Kalimantan were analyzed using the comprehensive assessment framework from September-December 2021. A literature review and discussion with experts, followed by a focus group discussion to perform a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis was conducted. The complex problem identifies and defines the relevant Economic, Ecological, and Societal (EES) issues, and inclusive identification and analysis of relevant stakeholders were described. Issues identified during the process were translated into relevant indicators in the EES sustainability dimensions then indicators possible for EES issues were proposed. Situation analysis in this study described and identified swamp buffalo in South Kalimantan, which is currently experiencing a population decline. The gross margin and growth and reproduction performances of the buffaloes were selected for economic benefit in both systems. Total land use and soil fertility were the possible indicators in the dimension of environment relevant for DPS, while swamp sedimentation and water pollution were considered important environmental indicators in SPS. Feed availability was measured in both systems. Social dimension indicators in both systems were focused on keeping management, the function of buffalo for livelihood, time allocation to keep buffalo, characteristics of livelihood, and possible land use conflicts.